ATF4 Degradation Relies on a Phosphorylation-Dependent Interaction with the SCF(βTrCP) Ubiquitin Ligase - Lassot, Irina (American Society for Microbiology, 2001)
The ubiquitin-proteasome pathway regulates gene expression through protein degradation. Here we show that the F-box protein βTrCP, the receptor component of the SCF E3 ubiquitin ligase responsible for IκBα and β-catenin degradation, is colocalized in the nucleus with ATF4, a member of the ATF-CREB bZIP family of transcription factors, and controls its stability. Association between the two proteins depends on ATF4 phosphorylation and on ATF4 serine residue 219 present in the context of DSGXXXS, which is similar but not identical to the motif found in other substrates of βTrCP. ATF4 ubiquitination in HeLa cells is enhanced in the presence of βTrCP. The F-box-deleted βTrCP protein behaves as a negative transdominant mutant that inhibits ATF4 ubiquitination and degradation and, subsequently, enhances its activity in cyclic AMP-mediated transcription. ATF4 represents a novel substrate for the SCF(βTrCP) complex, which is the first mammalian E3 ubiquitin ligase identified so far for the control of the degradation of a bZIP transcription factor.